Fiber Optic Micro-Hole Salinity Sensor Based on Femtosecond Laser Processing - Chen Li; Chao Fan; Hao Wu; Xxx Sedao; Jiang Wang (Nanomaterials)
This study presents a novel reflective fiber Fabry–Perot (F–P) salinity sensor. The sensor employs a femtosecond laser to fabricate an open liquid cavity, facilitating the unobstructed ingress and egress of the liquid, thereby enabling the direct involvement of the liquid in light transmission. Variations in the refractive index of the liquid induce corresponding changes in the effective refractive index of the optical path, which subsequently influences the output spectrum. The dimensions and quality of the optical fiber are meticulously regulated through a combination of femtosecond laser cutting and chemical polishing, significantly enhancing the mechanical strength and sensitivity of the sensor’s overall structure. Experimental results indicate that the sensor achieves salinity sensitivity of 0.288 nm/% within a salinity range of 0% to 25%. Furthermore, the temperature sensitivity is measured at a minimal 0.015 nm/°C, allowing us to neglect temperature effects. The device is characterized by its compact size, straightforward structure, high mechanical robustness, ease of production, and excellent reproducibility. It demonstrates considerable potential for sensing applications in the domains of biomedicine and chemical engineering.